Follicular flushing versus direct aspiration in poor responder IVF patients: a randomized prospective study. (May 2020) - Calabre, C.; Schuller, E.; Goltzene, M-A.; Rongières, C.; Celebi, C.; Meyer, N.; Teletin, M.; Pirrello, O.
Abstract: Objective: To compare follicular flushing with a double-lumen needle with direct aspiration on the number of oocytes collected in a poor responder population in IVF. Study design: We conducted a randomized controlled prospective single-center study between March 2011 and June 2016 at the ART center in the Medico-Surgical and Obstetric Center in Schiltigheim, France. Patients undergoing IVF who had ≤ 4 follicles ≥ 14 mm on the day of HCG administration were recruited and then randomized to one of two groups : simple aspiration group (= NO FLUSH) with a single-lumen 17-gauge needle or follicular flushing group (= FLUSH) which underwent oocyte puncture with aspiration and follicular flushing with a double-lumen 17-gauge needle. The primary end-point was the number of oocytes collected. Secondary assessment criteria were the fertilization rate, the number of transferable embryos, the number of clinical pregnancies and their outcome. Results: 252 patients were included: 127 in the Flush group and 125 in the No flush The number of oocytes retrieved per patient was significantly lower in the FLUSH group: 2.41 than in the NO FLUSH group: 3.42 (p < 0.001). The number of transferable embryos, fertilization rate (68.8 % in the FLUSH group versus 75 % p = 0.682), or pregnancy rate weren't different but (15 versus 13). However the number of failed punctures was significantly higher in the FLUSH group (11 % versus 3.2 % p = 0.016) and the duration of oocyte retrieval was significantly longer in the FLUSH group where the median time was 10 min whereas it was only 7 min in the NO FLUSH group, p < 0.001 Conclusion: Follicular flushing in poor responders is not beneficial and could be detrimental with an increasing procedure time and less oocytes retrieved.